Studi Penggunaan Obat Antihipertensi Pada PasienPreeklampsia Berat di Instalasi Rawat InapRumah Sakit Daerah Dr. Moewardi SurakartaTahun 2014 - AMRI, MUHAMMAD ULIL; , Dra. Nurul Mutmainah, M.Si., Apt (2015)
Preeclampsia is a form of hypertension in pregnancy is defined as hypertension with proteinuria, is a multisystem disorder that occurs after 20 weeks gestation. This study aims to know the description of antihypertensive use in patients with severe preeclampsia and to determine the accuracy of antihypertensive severe preeclampsia in RSUD Dr. Moewardi Surakarta review of aspects of the right indication, the right drug, right patient and the right dose of the reference standard POGI 2006. The type of research is included in this type of non-experimental research, because it does not give any treatment to the subjects of the study. Research conducted observational data were taken retrospectively and analyzed by descriptive non analytic. The samples used were patient RSUD Dr. Moewardi Surakarta who suffered severe preeclampsia and the use of antihypertensive therapy and met the inclusion criteria specified. The 76 patients using antihypertensive no pregnant women who suffer severe preeclampsia in Inpatient RSUD Dr. Moewardi Surakarta in 2014 were analyzed with reference standards POGI 2006 and BNF 54, obtained 49.19% meet the criteria for proper indications, 81.35% meet the criteria for proper medication, 86.44% meet the criteria for appropriate dose, 93.22% met the criteria the right of patients and the percentage of cases that rational treatment is 40.67%.